Enhancing the international appeal of Chinese culture through the looking China Youth Film Project: a cese study at Sanxingdui - Xinya, Huang; Zhuofan, Yang (International communication of Chinese culture, 2023)
Looking China Youth Film Project, founded in 2011 by Mrs. Huang Huilin, a senior professor at Beijing Normal University, aims to complete a 10-min documentary film on Chinese culture through the unique perspective of international young filmmakers, with the one-on-one cooperation of Chinese volunteers, to highlight the independent creativity and unique experience of foreign youth, thus enhancing the international influence and appeal of Chinese culture. The video works on China produced by young international filmmakers from the perspective of the "other" represents the confluence of cultures, the collision, and the acceptance of values among various countries. This paper takes the Looking China Youth Film Project Sanxingdui as an example, and discusses the concept of the "other" from the perspective of the culture of the "other", as well as the barriers to cross-cultural communication and the transfer of values in its perspective, in the hope that it can better contribute to Chinese culture going global.